Malnutrition and cognitive impairment among people aged 60 years and above living in regular housing or in special housing in Sweden: a population-based cohort study. Issue 2 (3rd January 2012) - Geurden, Bart
Abstract : Commentary on: Fagerström C Palmqvist R Carlsson J . Malnutrition and cognitive impairment among people 60 years of age and above living in regular housing and in special housing in Sweden: a population-based cohort study. Int J Nurs Stud 2011 ;48 (7 ):863 –71 .